(3GdgLf GdYQHjI GdCUjdI (B:s (3OQGSI JMdjdjI Yf gLf GdSHGb aj bWQ (B/s - (3Ydj, MSf CMeOs; (3GdWMGf, YGOd aGQhbs ((3GdOhMI (B:s (3OGQ GdKbGaI ddWHGYI hGdfTQ hGdJhRjY, bSe GdcJGH,s, 2001)
(3jJfGhd GdcJGH cd eG jNU gLf GdSHGb aj bWQ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3HHdjhLQGajI (B: (3UaMI (B131-132.s
Keywords: (3GdEHds -- (3JQHjIs -- (3bWQs; (3GdMjhGfGJ GdUMQGhjIs -- (3bWQs